Peri‐zygomatic infection associated with zygomatic implants: A retrospective longitudinal cohort study. Issue 4 (15th February 2022) - Vrielinck, Luc; Moreno‐Rabie, Catalina; Schepers, Serge; Van Eyken, Peter; Coucke, Wim; Politis, Constantinus
Abstract: Objectives: The main objective of this retrospective, longitudinal, cohort study was to describe the occurrence of peri‐zygomatic infection (PZI) as a complication associated with zygomatic implant (ZI) placement in a period of 22 years. Materials and methods: A retrospective search was carried out in the department of oral and maxillofacial surgery of Saint John's hospital in Genk, Belgium. Patients that had a severely atrophic fully or partially edentulous maxilla, and at least one ZI placed, were included. Results: A total of 302 eligible patients, underwent ZI surgery between 1998 and 2020. From a total of 940 ZI, 45 were associated with the development of PZI. PZI was located in the upper portion of the cheek in relation to the external corner of the eye, one or two centimeters under the lower lid. The total number of affected patients was 25 (8.3%), who had a mean age of 58.1 years. In this subset, PZI occurred in 15 cases on the right side, in eight cases on the left side, and in two cases bilaterally. Ultimately, 16 ZI were lost in the PZI site. The mean time since the implant placement to the diagnosis of PZI was 1.9 years (SD ±2.4) and to the ZI removal of 3.8 years (SD ±3.7). After implant removal, the PZI symptomatology dissipated in all patients. Conclusion: Peri‐zygomatic infection should be informed to the patients as a possible complication after ZI placement. Once identified, it should be acknowledged as a risk factor for ZI failure.